2016
DOI: 10.1523/eneuro.0248-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synaptic Excitation and Abnormal Dendritic Structure of Prefrontal Cortex Layer V Pyramidal Neurons following Prolonged Binge-Like Consumption of Ethanol

Abstract: Long-term alcohol use causes a multitude of neurochemical changes in cortical regions that facilitate the transition to dependence. Therefore, we used a model of long-term, binge-like ethanol consumption in rats to determine the effects on morphology and synaptic physiology of medial prefrontal cortex (mPFC) layer V pyramidal neurons. Following 10 weeks of ethanol consumption, we recorded synaptic currents from mPFC neurons and used neurobiotin filling to analyze their morphology. We then compared these data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…As the present findings indicate that voluntary EtOH differentially affects subtypes of PFC pyramidal cells, we fully expect distinct adaptations across the anatomically and molecularly varied cortical layers. Here, in layer 5, we observed increased synaptic strength in a subset of pyramidal cells, consistent with the modest effect observed by Klenowski and colleagues (2016). We also believe these findings are not inconsistent with the negative results obtained by Cannady and colleagues (2020), considering the effect size, cell type specificity, and additional methodological considerations.…”
Section: Discussionsupporting
confidence: 92%
“…As the present findings indicate that voluntary EtOH differentially affects subtypes of PFC pyramidal cells, we fully expect distinct adaptations across the anatomically and molecularly varied cortical layers. Here, in layer 5, we observed increased synaptic strength in a subset of pyramidal cells, consistent with the modest effect observed by Klenowski and colleagues (2016). We also believe these findings are not inconsistent with the negative results obtained by Cannady and colleagues (2020), considering the effect size, cell type specificity, and additional methodological considerations.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in nondependent excessive drinkers have suggested that alcohol‐induced changes in behavior are linked to changes in the corticolimbic system (Arienzo et al, 2019; Cservenka and Brumback, 2017; de Guglielmo et al, 2016; Hu et al, 2018; Klenowski et al, 2016), with rodent studies establishing this with neurotrophic factors, neurotransmitters, and neuropeptides (Darcq et al, 2015; George et al, 2012; Ketchesin et al, 2016; Lee et al, 2018). Although these studies used drinking models that yielded overall high EtOH consumption, it remains unclear how these neurobiological changes may manifest differently with the higher compared to lower drinking that occurs within a heterogenous population.…”
supporting
confidence: 91%
“…B,B′). Representative tracings were taken from NeuroExplorer (MBF Bioscience Inc.) and projected in the xy plane, in a manner similar to past studies (Bandaru et al, ; Klenowski et al, ; Williams et al, ).…”
Section: Methodsmentioning
confidence: 99%